Investigation of electricity production feasibility in Tabriz using biomass resources - Mahin Tahmasebpour; Abdollah Jafarian (Institute of Advanced Engineering and Science, 2013)
In this research, the feasibility of biogas production using biomass in collected wastes is studied. In this paper, first the different methods of recycling energy and for most used algorithms are studied. Second, by analyzing daily collected wastes and considering the realistic obtained data from leachate of Tabriz waste landfills, the average amount of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) are obtained. Then, an appropriate scenario is presented to get the maximum reachable biogas. Also, an economic model taking into account the effect of main variables of preparations such as the cost of waste transport vehicles, capacity of the purchased devices, special costs of biomass and distributed density are considered and the best and most economical method is utilized based on generated gas volume in biomass power plants. Finally, the shortterm and long-term models are presented for power generation and investment using biogas. The proposed method is applied for the wastes of Tabriz City, as one of the largest industrial metropolitan in Iran, with a daily waste more than 1200 tons.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2622